Dimensions of Inequality in Urban and Rural Water, Sanitation and Hygiene Services in Sub-Saharan Africa - Ohwo, Odafivwotu (European Scientific Journal, ESJ, 2019)
The attainment of the Sustainable Development Goals (SDGs) for water, sanitation and hygiene (WASH) requires the elimination of all forms of inequalities in WASH services. Hence, this study was aimed at the assessment of the dimensions of inequality in urban and rural WASH services in sub-Saharan Africa. This study adopted a descriptive design based on secondary data obtained from the 2015, Joint Monitoring Programme (JMP) report that contains global estimates on WASH services. The obtained data were presented in tables and analyzed using percentages. The study revealed that generally there exist inequalities in WASH services at different levels in the region and particularly between urban and rural areas. These disparities are threats toward the attainment of the SDGs for WASH in the region. To avoid these threats, all countries in the region must develop WASH policies that eliminate inequalities to WASH services, promote education and alleviate poverty; reduce corruption in the WASH sector and develop the capacity of institutions charged with WASH services with improved funding and accountability.